Thermal and hydrolytic degradation of electrospun fish gelatin membranes - Correia, D.M. (2013)
The thermal and hydrolytic degradation of electrospun gelatin membranes cross-linked with glutaraldehyde in vapor phase has been studied. In vitro degradation of gelatin membranes was evaluated in phosphate buffer saline solution at 37 ºC. After 15 days under these conditions, a weight loss of 68 % was observed, attributed to solvation and depolymerization of the main polymeric chains. Thermal degradation kinetics of the gelatin raw material and as-spun electrospun membranes showed that the electrospinning processing conditions do not influence polymer degradation. However, for cross-linked samples a decrease in the activation energy was observed, associated with the eﬀect of glutaraldehyde cross-linking reaction in the inter- and intra-molecular hydrogen bonds of the protein. It is also shown that the electrospinning process does not affect the formation of the helical structure of gelatin chains.